Ethical Issues in Conducting Qualitative Research in Online Communities - Roberts, Lynne (Routledge, 2015)
Increasingly, psychologists are extending their research to include online methods of data collection. Psychologists’ use of qualitative data obtained or generated online for research purposes poses unique challenges because of the “traceability” of quotes, often sensitive content of data and potential impact on both individuals and online communities. In this article, working within a framework that goes beyond “procedural ethics” to examine “ethics in practice,” ethical issues associated with conducting qualitative research within online communities are identified. These include tensions over public/private space, authorship versus human research participants, informed consent, anonymity and pseudonymity, covert research, deceptive research identities, reactions to being researched, and the quality of data obtained. Prior to conducting qualitative research in online communities, researchers have an ethical obligation to identify and weigh possible risks and benefits to both the community and community members. Sensitivity to the specific online community and continued ethical consideration throughout the conduct and reporting of the research are required.